Neonatal Immunization: Rationale, Current State, and Future Prospects - Whittaker, Elizabeth; Goldblatt, David; McIntyre, Peter; Levy, Ofer (Frontiers in Immunology, 2018)
Infections take their greatest toll in early life necessitating robust approaches to protect the very young. Here we review the rationale, current state and future research directions for one such approach: neonatal immunization. Challenges to neonatal immunization include natural concern about safety as well as a distinct neonatal immune system that is generally polarized against Th1 responses to many stimuli such that some vaccines that are effective in adults are not in newborns. Nevertheless, neonatal immunization could result in high population penetration as birth is a reliable point of healthcare contact, and offers an opportunity for early protection of the young, including preterm newborns who are deficient in maternal antibodies. Despite distinct immunity and reduced responses to some vaccines, several vaccines have proven safe and effective at birth. While some vaccines such as polysaccharide vaccines have little effectiveness at birth, hepatitis B vaccine (HBV) can prime at birth and requires multiple doses to achieve protection, whereas the live attenuated Bacille Calmette Guérin (BCG), may offer single shot protection, potentially in part via heterologous (“nonspecific”) beneficial effects. Additional vaccines have been studied at birth including those directed against pertussis, pneumococcus, Haemophilus influenza type B (Hib) and rotavirus providing important lessons. Current areas of research in neonatal vaccinology include characterization of early life immune ontogeny, heterogeneity in and heterologous effects of BCG vaccine formulations, applying systems biology and systems serology, in vitro platforms that model age-specific human immunity and discovery and development of novel age-specific adjuvantation systems. These approaches may inform, de-risk and accelerate development of novel vaccines for use in early life. Key stakeholders, including the general public, should be engaged in assessing the opportunities and challenges inherent to neonatal immunization.